Planning, organization and provision of independent work of students - Koksharova M. V., Belchikova O. G. (Socio-Pedagogical Issues of Education and Upbringing, 2023)
Students, upon admission to the university, find themselves in completely new conditions for them, in which the bulk of the study time falls on independent work, and the main control over educational activities is carried out at the end of the semester. And this means that they are not able to independently acquire knowledge without special training and special training. The authors give recommendations on the organization of independent work of students: to determine the complexity of tasks; deadlines for issuance and execution; tasks should be individual and have the nature of a professional orientation
Keywords: высшее образование; higher education; контроль; самостоятельная работа студентов; independent work of students; control; профессиональная направленность; individual and professional orientation; индивидуальная направленность